Identification of a novel biomarker of antibody-mediated rejection in heart transplantation: synergistic effect of anti-nuclear antibodies and de novo donor-specific IgG HLA antibodies - Maneesh Kumar Misra; Maneesh Kumar Misra; Phillip McMullen; Gene H. Kim; Susana G. Marino (Frontiers in Immunology)
IntroductionHumoral autoimmune response may play a significant role in stimulating the alloimmune response, leading to antibody-mediated rejection (ABMR). This study investigated whether the development of IgG de novo donor-specific antibodies (dnDSA) could serve as an independent marker for ABMR diagnosis. Subsequently, we evaluated the synergistic effects of non-HLA anti-nuclear antibodies (ANA) and circulating IgG anti-HLA dnDSA in the development of ABMR.MethodsThis retrospective study included 285 patients who underwent heart transplants between January 2007 to November 2020 at the University of Chicago Medical Center and who had sufficient serum collected at the time of protocol or indication biopsy available for antibody testing.ResultsWe observed a 23% incidence of ABMR in heart transplant patients at our center. Kaplan–Meier survival analysis revealed the lowest ABMR free survival in recipients that were positive for both ANA and circulating IgG dnDSA (Log rank p = 2 x 10-16), indicating a synergistic effect of ANA and circulating IgG dnDSA. A univariate stepwise cox proportional hazard model establishes the presence of IgG dnDSA as an independent marker to predict ABMR diagnosis (HR = 8.70, p = 6.15 x 10-9). Similarly, a synergistic effect was found in the presence of a positive ANA titer and IgG dnDSA for ABMR diagnosis in a univariate model (HR = 13.1, p = 2.73 x 10-14). A multivariate stepwise cox proportional hazard model showed an almost seven-fold increased risk for ABMR in patients that have developed IgG dnDSA (HR = 6.96, p = 2.33 x 10-6). Similarly, nearly an eleven-fold enhanced risk for ABMR was found in heart transplant recipients who were positive for ANA and had developed de novo IgG DSA (HR = 10.7, p = 1.25 x 10-10), suggesting the synergistic effect of ANA and IgG dnDSA in ABMR diagnosis.DiscussionThis study establishes circulating IgG dnDSA as an independent biomarker for ABMR diagnosis in heart transplantation and confirms the previously known correlation of IgG dnDSA with ABMR. Subsequently, our data revealed that circulating IgG dnDSA and non-HLA antinuclear antibodies have synergistic effects that cause antibody-mediated rejection in heart transplantation.